The Effect of Aceh Government Spending Policy on Inclusive Growth: Income per Capita as a Mediating Variable - Saputra, M. Eka; Zulham, Teuku; Srinita, Srinita (Grimsa Journal of Business and Economics Studies, 2025)
In 2021, inclusive growth in Aceh Province, Indonesia, as measured by the Inclusive Economic Development Index (IPEI), declined compared to the ranking achieved in 2011. Government intervention through spending policy faces new challenges, particularly due to a decrease in the allocation of the special autonomy fund (OTSUS) in 2022, which is set to fully end in 2027. This study aims to analyze the effect of local expenditure policies implemented by the Aceh government, using per capita income as a mediating variable. The analysis was conducted using the Random Effects Model (REM) and panel data from 23 districts/cities from 2011 to 2021. The results show that capital expenditure and social assistance expenditure negatively impact inclusive growth, whereas grant expenditure and per capita income have a positive effect. Additionally, the findings indicate that per capita income mediates the impact of capital expenditure on inclusive growth but does not mediate the effects of grant expenditure or social assistance on inclusive growth. Therefore, it is necessary to improve governance, budgeting policies, and regional expenditures in a more sustainable and targeted manner to promote inclusive growth and achieve more equitable welfare for all people in Aceh Province.